A Descriptive Study on the Effectiveness of the Scan-and-Learn Mobile Application in Enhancing Knowledge, Skills, and Engagement in Technical and Vocational Education - Regie Boy B. Fabro; Shanyna Jade A. Tambio (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study examines the effectiveness of the Scan-and-Learn Mobile App in enhancing Grade 7 students’ learning outcomes in Technical and Vocational Education (TVE), focusing on their knowledge and skills related to kitchen tools and equipment. The research addresses the challenge of limited access to physical resources in schools by exploring how mobile learning technology can support teaching and learning in resource-constrained environments. Using descriptive research methods, data were collected from 71 student respondents through surveys that included both closed-ended and open-ended questions. The responses were analyzed using weighted means to evaluate the app’s impact across five components: knowledge, skills, engagement and motivation, perceived usefulness, and satisfaction. The findings reveal that the app significantly improves students’ knowledge and understanding of kitchen tools, as well as their practical skills in operating kitchen equipment. Students report high levels of engagement and motivation, emphasizing the app’s interactive features, such as step-by-step instructional videos and scanning tools, as key factors in making learning enjoyable and effective. The app is also perceived as a highly useful supplementary tool for reinforcing classroom learning, providing quick access to information, and fostering independent study. However, the study notes that while the app enhances understanding and skill development, hands-on practice is essential to further improve students’ ability to apply their skills accurately in real-world scenarios. The study concludes that the